Common Fixed Point Results for Three Multivalued \(ρ\)-Nonexpansive Mappings by Using Three Steps Iterative Scheme - Morwal, Reena; Panwar, Anju (Communications in Mathematics and Applications, 2020)
The purpose of this research paper is to study the convergence and approximation of common fixed points for three multivalued \(ρ\)-nonexpansive mappings for three steps iterative scheme in modular function spaces. Further we construct a numerical example which illustrates our results.
Keywords: Common fixed point; Multivalued ½-nonexpansive; Three steps iterative scheme; Modular function spaces